Penguatan Kompetensi Literasi Digital Pelajar melalui Pelatihan Konten Kreatif untuk Promosi Pariwisata Lokal Desa Wisata - Suryani Suryani; Latifah Latifah; Nurul Giswi Karomah; Istna Fibriyadi; Widiyono Widiyono (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aims to improve the digital literacy of students in Bantar Agung Tourism Village, Majalengka Regency, West Java, through training in creative content production as a means of regional promotion. The activity is motivated by the underutilized potential of local tourism in the digital space, as well as the limited skills of students in using social media productively. The methods employed include counseling, hands-on training, and intensive mentoring in creating digital content, such as photography, videography, caption writing, and social media platform management. The participants are junior and senior high school students residing in Bantar Agung Village..The results of the program indicate an increase in participants’ understanding of digital literacy concepts, media ethics, and technical skills in producing engaging and informative creative content 86 %. In addition, participants are able to produce and publish promotional content about the village’s tourism through various digital platforms, thereby contributing to increased visibility of Bantar Agung as a tourist destination. Continuous mentoring has also encouraged the formation of a village youth creator community that actively participates in regional promotion..Thus, this training program not only enhances students’ digital competencies but also generates a positive impact on the development of community-based local tourism potential. This activity is expected to serve as a model for empowering rural students through sustainable and adaptive digital literacy in response to technological advancements